Hubungan Antara Laba Perusahaan Dan Kompensasi Ceo Dengan Menggunakan Data Panel - Tiarapuspa Tiarapuspa (Universitas Airlangga, 2008)
The main purpose of this research is to explain the relationship between profit and CEO compensation. The relationship between CEO compensation and company profit in 1992-1996 from 32 firms that listed in Jakarta Stock Exchange has a different result. Some researches find that there is a significant relationship but in the other hand find there isn’t a significant relationship. This result support generalization or validity external from previous research. This research used panel data to examination this relationship.